Penile fracture: immediate surgical intervention and postoperative outcomes - Azzuz, Shahirah; Faydh, Jamal; Hussain, Ali; Jassim, Faisal; Almtotah, Abdullah; Mandani, Hussain; Alshammari, Abdulaziz; Almehini, Hamad; Alharthi, Yazeed (International Journal Of Community Medicine And Public Health, 2025)
Penile fracture is a rare but urgent urological emergency characterized by rupture of the tunica albuginea, typically following blunt trauma to an erect penis. Clinical features often include an audible crack, sudden detumescence, penile pain, and swelling. Surgical repair within the first 24 hours remains the preferred treatment, associated with improved functional recovery and reduced risk of long-term complications. Delayed presentation increases the likelihood of fibrosis, curvature, erectile dysfunction, and infection. Various surgical techniques are employed depending on the location and extent of injury, with the subcoronal degloving incision offering optimal exposure in most cases. The choice of suture material, thorough evacuation of hematoma, and evaluation of associated urethral injury significantly influence outcomes. Postoperative complications range from minor hematomas and wound infections to more significant sequelae such as penile curvature, palpable plaques, voiding dysfunction, and psychogenic erectile dysfunction. Bilateral corporal rupture and urethral involvement predict poorer recovery and often require more complex surgical intervention. Objective measures such as IIEF scores are commonly used to assess erectile function, but subjective satisfaction often depends on psychological resilience and partner dynamics. Factors such as early intervention, patient age, baseline comorbidities, and extent of injury serve as key predictors of postoperative recovery. Long-term follow-up highlights the importance of not only preserving anatomical integrity but also addressing emotional and sexual health. Patient education, timely diagnosis, and individualized surgical management are central to optimal outcomes in penile fracture care.